Association of lipoprotein(a) with platelet aggregation and thrombogenicity in patients undergoing percutaneous coronary intervention. (4th July 2021) - Zhu, Pei; Tang, Xiao-Fang; Song, Ying; Zhang, Yin; Gao, Li-Jian; Gao, Zhan; Chen, Jue; Yang, Yue-Jin; Gao, Run-Lin; Xu, Bo; Yuan, Jin-Qing
Abstract: This study aimed to evaluate the association of lipoprotein(a) levels with platelet aggregation and thrombogenicity in patients undergoing percutaneous coronary intervention (PCI), and to investigate the ischemic outcome on this population. Lipoprotein(a) and modified thrombelastography were measured in 6601 consecutive patients underwent PCI on dual antiplatelet therapy. Cox proportional regression analysis was applied to illustrate the ischemic events in a 2-year follow up. The mean levels of lipoprotein(a) were 29.0 mg/dl. Patients with higher lipoprotein(a) levels had significantly accelerated fibrin generation (lower K time and bigger α angle) and greater clot strength (higher maximum amplitude (MA)) than patients with lower lipoprotein(a) levels ( P < .001). Moreover, the higher lipoprotein(a) group also exhibited significantly higher adenosine diphosphate (ADP) induced platelet aggregation (MAADP ) by thrombelastography platelet mapping assay than lower lipoprotein(a) group. Cox regression analyzes revealed that patients with higher lipoprotein(a) levels had a 16% higher risk of major adverse cardiovascular and cerebrovascular events (HR 1.159, 95%CI: 1.005–1.337, P = .042) compared with patients with lower lipoprotein(a) levels. This association persisted after adjustment for a broad spectrum of risk factors (HR 1.174, 95%CI: 1.017–1.355, P = .028). High plasma lipoprotein(a) levels were associated with increased platelet aggregation and ischemic events in patients underwent PCI. Lipoprotein(a) might indicate the need for prolonged antiplatelet therapy.